Biochemical, Physicochemical and Sensory Properties of Yoghurts Made from Mixing Milks of Different Mammalian Species - Oumayma Boukria; El Mestafa El Hadrami; Aysha Sameen; Amna Sahar; Sipper Khan; Jasur Safarov; Shakhnoza Sultanova; Françoise Leriche; Abderrahmane Aït-Kaddour (Foods, 2020)
Among developed countries, bovine milk production makes a major contribution towards the economy. Elevating consumer demand for functional foods has triggered a niche for non-bovine milk-based products. Mixing milks from different species can be a strategy to increase the consumption of non-bovine milk and enable consumers and dairy companies to benefit from their nutritional and technological advantages. Thus, this review aimed to gather the most important research on yoghurts derived from processing mixtures of milks of different species. We discuss the impact of milk mixtures (i.e., species and milk ratio) on nutritional, physicochemical, sensory, rheological and microbiological properties of yoghurts. More specifically, this paper only highlights studies that have provided a clear comparison between yoghurts processed from a mixture of two milk species and yoghurts processed from a single species of milk. Finally, certain limitations and future trends are discussed, and some recommendations are suggested for future research.